The Students' Grammatical Mistakes in Writing Narrative Text - Maitri Ramadhani; Windy Mutiara Ananda (LPPM STKIP AL MAKSUM, 2020)
Students made errors in writing narrative text. Two reasons why students made errors were because less grammar mastery and confuses to differentiate the verb. This writing is to find out the grammatical errors. The method of research is descriptive quantitative. The process of data is analyzed by reading students’ writing first, identifying, classification, tabulating, describing, and taking conclusion about the errors. After analyzing the data, it was found that students made errors in omission, addition, misformation, and misordering categories. The highest frequency of item error was in using a verb tense with a total of 61 errors. Meanwhile, the lowest frequency of item errors was in using adverbs and adjective with a total of 6 errors. The total of the errors was 204. Keywords: Conjunction; Article; To be; Verb Tense; Pronoun.